Brain-derived neurotrophic factor (BDNF) in the hypothalamic ventromedial nucleus increases energy expenditure - Wang, ChuanFeng (Brain Res, 2010)
Brain-derived neurotrophic factor (BDNF) decreases food intake and body weight, but few central sites of action have been identified for its effect on energy expenditure. The hypothalamic ventromedial nucleus (VMH) is important in regulating energy metabolism. Our previous work indicated that BDNF in the VMH reduced food intake. The purposes of the study were to determine: 1) if BDNF in the VMH increases energy expenditure (EE); 2) if BDNF-enhanced thermogenesis results from increased spontaneous physical activity (SPA) and resting metabolic rate (RMR); and 3) if VMH BDNF thermogenic effects are mediated by uncoupling protein 1 (UCP1) in brown adipose tissue (BAT). BDNF (0.5 μg) was injected into the VMH of male Sprague Dawley rats and oxygen consumption, carbon dioxide production, food intake and SPA were measured for 24 h in an indirect calorimeter. Animals were sacrificed 4 h after BDNF injection, and BAT UCP1 gene expression was measured with quantitative real-time polymerase chain reaction. BDNF significantly decreased food and water intake, and body weight gain. Heat production and RMR were significantly elevated for 9 h immediately after BDNF injection. BDNF increased SPA and aEE within 9 h after injection although BDNF had no effect on 0–24h SPA and EE during SPA (aEE). BDNF did not induce a significant increase in BAT UCP1 expression. In conclusion, VMH BDNF reduces body weight by decreasing food intake and increasing EE consequent to increased SPA and RMR, suggesting that the VMH is an important site of BDNF action to influence energy balance.